DEGRADASI LIMBAH CAIR KELAPA SAWIT DENGAN PENAMBAHAN BAKTERI RIZOSFIR Actinomycetes DAN TANAMAN Typha angustifolia DENGAN MODEL CONSTRUCTED TREATMENT WETLAND (CTW) - Suwondo ' '; Sri Wulandari '; Syaiful Ansha ' (Biogenesis, 2014)
Conducted a research to find the effectiveness of rhizosphere Actinomycetes bacteriaand Typha angustifolia plant addition to degrade palm oil liquid waste. Researchdesign using Constructed Treatment Wetlands models (CTW). The Parametersmeasured is the content of Chemical Oxygen Demand (COD), Biological OxygenDemand (BOD), Total Suspended Solid (TSS), the detention time, pH andtemperature. The results of this research showed that the Actinomycetes is a potentialmicrobe in degrading liquid waste. The use of Constructed Treatment Wetland (CTW)model is effective in degrading palm oil liquid waste with average content become432 mg/L for COD, 10 mg/L for BOD and 40 mg/L for TSS before it throws away tothe environment. The longer the detention time the content of COD and BOD will bereduced to 252 mg/L for COD and 23 mg/L for BOD.Keywords: Palm Oil liquid waste, Actinomycetes, Typha angustifolia, COD, BOD,TSS, CTW